AN ANALYSIS OF CONSUMER SATISFACTION WITH MOBILE TELECOM SERVICES AND THEIR IMPACT ON SUBSCRIBERS IN NAGPUR CITY - Dange, Kalyani; Chib, Shiney (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Indian economy is a developing economy. Various sectors contribute to the development of the economy telecommunication is one of these sectors in the boom. The Telecom industry is contributing a lot toward technological innovation, with the help of digitalization telecom industries are providing various facilities to their customers to serve them and attract them so that to get various subscriber bases, with the effect of those services on its subscribers a research study has been undertaken in the city of Nagpur. To recognize the purchaser's delight toward cellular telecom offerings supplied through distinct telecom providers. This study additionally researched diverse components that display the effect of nice offerings on purchaser retention. Recently, the industry has experienced a significant transformation as consumers have increasingly moved from fixed-line services to wireless options. The main aim of the study is to focus on the quality of service provided by telecom operators and its effect on the sales revenue of the company and help them to forecast future profitability as well as make them aware of providing more and more satisfying services to their consumers to retain them for a longer period for a better future prospectus.